2013
DOI: 10.5732/cjc.013.10178
|View full text |Cite
|
Sign up to set email alerts
|

Fusion genes in solid tumors: an emerging target for cancer diagnosis and treatment

Abstract: Studies over the past decades have uncovered fusion genes, a class of oncogenes that provide immense diagnostic and therapeutic advantages because of their tumor-specific expression. Originally associated with hemotologic cancers, fusion genes have recently been discovered in a wide array of solid tumors, including sarcomas, carcinomas, and tumors of the central nervous system. Fusion genes are attractive as both therapeutic targets and diagnostic tools due to their inherent expression in tumor tissue alone. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 92 publications
0
71
0
Order By: Relevance
“…Fusion genes play a critical role in investigating causes and development of various cancer types 56 . RNA-seq has been shown as a valuable source for detecting fusion genes 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Fusion genes play a critical role in investigating causes and development of various cancer types 56 . RNA-seq has been shown as a valuable source for detecting fusion genes 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Such gene-fusions can lead to chimeric proteins able to suppress tumour-suppressor genes or activate oncogenes and their assessment provides an opportunity to expand the available prognostic and treatment options (reviewed by Parker et al [224]).…”
Section: Cancer Somatic Mutation Analysismentioning
confidence: 99%
“…Studies over the past decades have uncovered the oncogenic role of fusion genes in hematological malignancies and mesenchymal tumors, and have highlighted the diagnostic and therapeutic advantages provided by the detection of these chimeric transcripts and their tumor‐specific expression 15. A similar search for fusion transcripts in ovarian cancer has shown that they are not common.…”
Section: Discussionmentioning
confidence: 99%